Class Analysis in Conditions of a Dual-Stratification Order. (August 2015) - Zarycki, Tomasz
This article presents a critique of classic applications of class analysis to Polish society. It argues from a Bourdieusian standpoint that class is subordinate to culture in shaping social relations in Poland. More specifically, Poland can be seen as a dual-stratification order, with the economic logic of class clashing continually with the logic of rank, which is defined in terms of cultural capital. These two models of logics appear to be in constant competition, which may also be related to the tension between economic and cultural elites. The latter is most clearly represented by the old intelligentsia, which is the only faction of the elite able to reproduce itself successfully and impose its logic of stratification and ideology on the entire society. The article also argues that class and rank logic can be seen as two dimensions of a social structure that are much more autonomous than in a typical western society. Within these two dimensions, there is a constant competition between different modes of framing and regulating respective hierarchies. In this internal competition of hierarchies, rank and class use each other to reinforce particular arguments. A sound class analysis must recognize these tensions and seek to reconstruct the process of confrontation between particular modes of logic and their internal visions, rather than arbitrarily embracing one form of logic as the privileged one.